Anticorrosive pigments based of perovskite with surface layer conductive polymer PPDA - Hájková, Tereza; Kalendová, Andréa (CHEMagazín, s.r.o., 2016)
The properties of protective organic coatings containing perovskites whose surface had been modified with conductive polymers were investigated, with focus on their anticorrosion effect. The perovskite type pigments (XYO3; X = Ca, Sr, Y = Ti, Mn) were synthesized by high-temperature solid-phase reaction, and their surface was modified with a conductive polymer, specifically polyparaphenylendiamine phosphate (PPDA), by chemical oxidative polymerisation. Conductive polymers are currently attracting considerable interest in a number of sectors, among them the paint industry owing to their non-toxicity and high stability. Paints consisting of a solvent-based epoxy-ester resin as the binder and the above-mentioned perovskite/PPDA pigments were formulated and subjected to mechanical tests in order to assess the effect of the composite pigment particles on the paints' mechanical resistance. Corrosion resistance of the coatings was tested also evaluated in dependence on the type of particle surface treatment with the conductive polymer, chemical composition of the pigment, and pigment volume concentration (PVC) in simulated corrosive atmosphere.
Antikorozní pigmenty na bázi perovskitů s povrchovou úpravou vodivým polymerem PPDA
Keywords: perovskites; anticorrosion pigment; organic coating; conductive polymer; epoxy-ester resin; paraphenylendiamine; perovskity; antikorozní pigment; organický povlak; vodivvý polymer; epoxy-esterová pryskyřice; parafenylendiamin